Legal Vacuums in the Submission of Notary Protocols - Erry Ariany; Azis Budianto (Syntax Idea)
This research discusses the legal protection of the immunity rights of advocates in the context of law enforcement in Indonesia. Advocate immunity is a legal guarantee provided to advocates to perform their duties independently and without fear of interference from others. This immunity is essential to ensure that advocates can provide effective legal defense for their clients without worrying about legal repercussions that could hinder the defense process. However, the implementation of advocate immunity rights in Indonesia still faces various challenges, including the potential for abuse of immunity and a lack of understanding among law enforcement regarding the limits of advocate immunity. In this article, the authors analyze the laws and regulations governing the rights of advocate immunity, as well as practical issues in the field related to the protection of these rights. By employing a normative approach and case analysis, this article offers recommendations to enhance legal protection of advocate immunity rights in the law enforcement process in Indonesia, alongside emphasizing the importance of education for law enforcement and the public regarding advocates' rights.